Mechanisms of electron scattering in uniaxially deformed n-Ge‹Sb, Au› single crystals - Luniov, S.V.; Nazarchuk, P.F.; Zimych, A.I.; Udovytska, Yu.A.; Burban, O.V. (Condensed Matter Physics, 2019)
Temperature dependencies for concentration and the Hall mobility of electrons for the n-GehSbi and n-GehSb, Aui single crystals uniaxially deformed along the crystallographic directions [100] and [111] are obtained on the basis of piezo-Hall effect measurements. A deformation-induced increase of the Hall mobility of electrons for n-GehSb, Aui single crystals at the uniaxial pressure along the crystallographic direction [100] has been revealed. A comparison of the obtained experimental results with the corresponding theoretical calculations of temperature dependencies of the Hall mobility showed that the obtained effect occurs at the expense of the reduction probability of electron scattering on the fluctuational potential. Its amplitude depends on the temperature and on the value of the uniaxial pressure. It has also been shown that an increase of the Hall mobility for the n-GehSb, Aui single crystals uniaxially deformed along the crystallographic direction [111] with an increasing temperature turns out to be insignificant and is observed only for the uniaxial pressures P < 0.28 GPa. A decrease of the Hall mobility of electrons at the expense of the deformational redistribution of electrons among the valleys of the germanium conduction band with different mobility should be taken into account in the present case. The Hall mobility magnitude for the uniaxially deformed n-GehSbi single crystals is determined only by the mechanisms of phonon scattering and we have not observed the effect of the growth of the Hall mobility with an increase of temperature or the magnitude of uniaxial pressure. This demonstrates a secondary role of the fluctuational potential in the present case.